A SOLUTION TO DETECT AND PREVENT WORMHOLE ATTACKS IN MOBILE AD HOC NETWORK - Tu, Vo Thanh; Ngoc, Luong Thai (Journal of Computer Science and Cybernetics, 2017)
Wormhole attack is one of varied types of Denial-of-Service attacks in Mobile Ad hoc Network. For purpose of attack, the attackers use the two malicious nodes connected with each other by a tunnel that is aimed at eavesdropping or damaging the data packet. Previous researches aiming at securing against the wormhole attacks was published, typical as detection algorithms based on Round Trip Time or Packet Traversal Time, or hop-count based analysis. They have the detection effectiveness is mitigated on the network topology with high mobility nodes, and depends on tunnel length. This article proposes a Valid Route Testing Mechanism (VRTM) and integration of VRTM into AODV protocol to make DWAODV which is able to detect and prevent the wormhole attacks. Using Network Simulator (NS2), we evaluate the security effectiveness of DWAODV protocol on random movement network topology at high speed. The simulation results shows that our solution is capable of detecting successfully over 99% of invalid routes, and small depend on tunnel length. In addition, in the normal network topology, the routing performance of DWAODV is approximately as AODV based on the metrics including the average length of each discovered routing path, packet delivery ratio, network throughput and routing load.